Teknologi Chatbot sebagai Alat Unggul dalam Pelayanan Referensi Perpustakaan - M. Yusuf (IJAL (Indonesian Journal of Academic Librarianship), 2024)
This article explores the role of chatbot technology as a forefront solution in enhancing the quality of library reference services. Confronting the need for innovation, particularly in providing efficient and responsive services for modern library users, chatbot technology becomes the focal point of the research. The background of the study highlights fundamental changes in the context of library services, where the development of information and communication technology emerges as a primary driver. The research aims to investigate the implementation of chatbots as a solution to improve the effectiveness of library reference services. Using the library research method, the study involves the analysis of literature and information sources related to the development and application of chatbot technology in the library environment. The results indicate that chatbot technology can significantly enhance the responsiveness and availability of library reference services. By offering instant and efficient access to information, chatbots weave a closer connection between the library and users. The conclusion of this article affirms that the integration of chatbots not only enriches the user experience but also propels the achievement of library goals in navigating the challenges of the ever-evolving digital era. Thus, chatbots are not just an innovation but also a superior tool capable of elevating library services to a higher level.